1995
DOI: 10.1002/star.19950471002
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite Oxidation of Barley and Potato Starch

Abstract: The oxidation of barley and potato starches was studied using sodium hypochlorite as oxidant. The degree of oxidation, depolymerization during oxidation and gel formation of barley starch was compared with the properties of potato starch. The effect of oxidation on gelatinization of starches as well as on amylose‐lipid complex of barley starch was also analyzed. Barley starch was not as easily oxidized as potato starch. In both starches depolymerization of amylopectin and amylose occurred during oxidation. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 24 publications
2
47
0
5
Order By: Relevance
“…The potency of starch granules increased which strengthens the diffusion of starch particles in water. [15] Similar trends of increased SP and solubility with increased temperature was found for millet starch [29] , barley and potato starch [34] , rice starch, [35] and corn starch. [36] The difference in structure of starch granules may contribute to variations within the SPs and solubility of different cereal starches.…”
Section: Sp and Solubility Of Starchessupporting
confidence: 69%
“…The potency of starch granules increased which strengthens the diffusion of starch particles in water. [15] Similar trends of increased SP and solubility with increased temperature was found for millet starch [29] , barley and potato starch [34] , rice starch, [35] and corn starch. [36] The difference in structure of starch granules may contribute to variations within the SPs and solubility of different cereal starches.…”
Section: Sp and Solubility Of Starchessupporting
confidence: 69%
“…Many studies have reported the influence of oxidation on the gelatinization properties of starch but the results are somewhat inconclusive and seem to depend on starch origin as well as the modification conditions. Forssell et al (1995) observed an increase in T o of oxidized barley starch, while the T o of oxidized potato starch remained unchanged. Wang and Wang (2003) reported an increase in T o of oxidized waxy and common corn starches, when a low concentration of hypochlorite (≤1.25% active chlorine) was used in the modification process.…”
Section: Discussionmentioning
confidence: 81%
“…Modifi cou-se o amido do taro por tratamento oxidativo com hipoclorito de sódio (NaOCl), conforme metodologia descrita por Forssel et al (1995). Preparou-se a pasta de amido a 50 g. 100 mL -1 , ajustando o pH para 9,5 com hidróxido de sódio a 2M.…”
Section: Modificação Por Oxidaçãounclassified